Etiology of severe acute respiratory infections in children hospitalized in hospitals of Ekaterinburg in the epidemic season of 2022 - 2023 - E. V. Lelenkova; I. A. Korotkova; A. Yu. Markaryan; E. V. Bolgarova; A. E. Chernysheva; P. I. Filatova; A. V. Semenov (LLC "Diagnostics and Vaccines", 2023)
Objective. Study of the viral etiology of severe acute respiratory infections (SARI) in children hospitalized in a hospital in Yekaterinburg during the epidemic season of 2022-2023. Materials and methods. 267 clinical samples (nasopharyngeal swab) obtained from children hospitalized with symptoms of acute respiratory disease were studied. The etiology of the disease was deciphered by RT-PCR, using standard sets of reagents. The material was examined for the presence of influenza A and B viruses, as well as for viruses of non-influenza etiology. 267 individual patient records were analyzed. Results. As a result, it was found that cases of SARI were more often registered among younger children, the structure of SARI of influenza etiology was represented by influenza A(H1N1)pdm09 virus - 29.9% and influenza B virus - 20.7%, while it was found that most children were not vaccinated against influenza. The proportion of viruses of non-influenza etiology was represented by RS viruses (23.0%), rhinoviruses (9.2%) and bokaviruses (6.3%).